ANALISIS TERHADAP DISPENSASI KAWIN YANG DIAJUKAN SENDIRI OLEH PEMOHON YANG BELUM CAKAP HUKUM (STUDI PUTUSAN : NOMOR 198/Pdt.P/2018/PA.Pwd). - Bunga Sakura; Mia Hadiati (Jurnal Hukum Adigama, 2021)
Marriage is a strong and firm agreement to live together legally between a man and a woman where the ideal marriage is a marriage in which both partners reach sufficient age. However, when one of the partners or both parties do not reach the age for marriage, the next step is to apply for a marriage dispensation. In this paper, there is a problem that will be discussed, namely how the status of the prospective bride and groom as an exempted marriage dispensation applicant.The purpose of this paper is to understand the status of the prospective bride and groom as an exempted marriage dispensation applicant. The research method used in this study is the normative research method. The research data was collected by means of literature study through the method of approaching laws and interviews. Then analyzed using qualitative analysis techniques. In terms of the status of the prospective bride and groom as an exempted marriage dispensation applicant is not legally competent. Child may not be the Petitioner in court because considering his age is still not legally competent. Court decisions made by judges have a major role in changing behavior and increasing legal awareness. It is necessary to have a common ground between the child protection law and the marriage law.